Tetrandrine Citrate Suppresses Breast Cancer via Depletion of Glutathione Peroxidase 4 and Activation of Nuclear Receptor Coactivator 4-Mediated Ferritinophagy - Yin, Jiameng; Lin, Yajun; Fang, Weiwei; Zhang, Xin; Wei, Jie; Hu, Gang; Liu, Pu; Niu, Jie; Guo, Jun; Zhen, Yongzhan; Li, Jian (Frontiers in Pharmacology, 2022)
Tetrandrine citrate (TetC), a novel tetrandrine salt with high water solubility, demonstrates a potent anti-tumor activity in chronic myeloid leukemia. Studies have indicated an important role of ferroptosis in breast cancer (BC). However, whether TetC inhibits BC progression via ferroptosis has never been explored. In the present study, we showed that TetC had a significant inhibitory effect on the proliferation and migration of MCF7 and MDA-MB-231 cells. Then, we combined TetC with different inhibitors to determine which form of cell death could be driven by TetC. MTT assay showed that ferrostatin (Fer-1) demonstrated most potent effect on improving TetC-induced cell death in contrast to other inhibitors. TetC was also shown to significantly reduce the mRNA level of prostaglandin-endoperoxide synthase 2 (Ptgs2), a ferroptosis marker. Further study showed that TetC significantly suppressed the expression of glutathione peroxidase 4 (GPX4) and ferritin heavy chain 1 (FTH1), but increased the expression of nuclear receptor coactivator 4 (NCOA4) in MCF7 and MDA-MB-231 cells even in the presence of erastin or Ras-selective lethal 3 (RSL3). Collectively, we showed novel data that ferroptosis was a major form of TetC-induced cell death. Moreover, TetC-induced ferroptotic cell death was achieved via suppressing GPX4 expression and activating NCOA4-mediated ferritinophagy in BC cells.